A rotary valve controlled electro-hydraulic vibration exciter. (December 2016) - Wang, He; Gong, Guofang; Zhou, Hongbin; Wang, Wei; Liu, Yi
When sinusoidal vibration waveform is required, the frequency bandwidth of conventional electro-hydraulic vibration exciter controlled by servo valve is always limited to a rather narrow range due to the limits of slide valve structure and response speed, and no parameter is available for defining and evaluating the waveform quality. In this paper, a novel electro-hydraulic vibration exciter controlled by electromotor driven rotary valve is proposed to significantly extend the frequency range compared to the conventional servo valve controlled counterpart. Total harmonic distortion (THD) theory which is usually used to cope with voltage and current in electric system is borrowed to evaluate the quality of theoretical and experimental vibration waveforms at different supply pressures and vibration frequencies, quantitatively and qualitatively. The results show that the waveform quality is mainly influenced by the 3rd harmonic resonance. The proposed vibration exciter can output sinusoidal waveform with THD less than 5% at the vibration frequency higher than 70 Hz. In this frequency domain, the supply pressure has an extremely low impact on the THD of the waveform. The amplitude of the waveform can be adjusted by changing the supply pressure with almost no effect to the waveform quality at a certain vibration frequency.